ĈAnĉ economic history of the Iberian Peninsula, 700-2000 - Lains, Pedro 1959-2021 (Cambridge Cambridge University Press, 2024)
This is a comprehensive long-run history of economic and political change in the Iberian Peninsula. Beginning with the development of the old medieval kingdoms, it goes on to explore two countries, Portugal and Spain, which during the early modern period possessed vast empires and played an essential role in the global economic and political developments. It traces how and why both countries began to fall behind during the first stages of industrialization and modern economic growth only to achieve remarkable economic development during the second half of the twentieth century. Written by a team of leading historians, the book sheds new light on all aspects of economic history from population, agriculture, manufacturing and international trade to government, finance and welfare. The book includes extensive new data and will be an essential work of reference for scholars of Portugal and Spain and also of comparative European economic development
E-Book/ Zugang nur im DHI-Lesesaal
Keywords: Spain / Economic conditions; Iberian Peninsula / Economic conditions; Portugal / Economic conditions